2008
DOI: 10.1159/000121335
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Improved Intracellular Calcium Handling in Hypoxia-Reoxygenated Cardiomyocytes via the Sarcoplasmic Reticulum Ca<sup>2+</sup>-ATPase

Abstract: Although astragaloside IV, a saponin isolated from Astragalus membranaceus, has been shown to protect the myocardium against ischemia/reperfusion injury, its effect on the status of sarcoplasmic reticulum (SR) Ca2+ transport in the injured myocardium remains largely unknown. In this study, we investigated whether in cultured cardiomyocytes subjected to hypoxia and reoxygenation (H/R) administration of astragaloside IV during H/R attenuates the myocardial cell injury and prevents changes in Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 42 publications
1
51
0
1
Order By: Relevance
“…Otherwise, HO-1 has been further demonstrated to be induced by dobutamine and inhibit HMGB1 release during myocardial I/R injury [11]. Importantly, cultured neonatal cardiomyocytes may present with a very stable phenotype and the contractile profile of cultured neonatal cardiomyocytes during H/R has been proved to be comparable with that of in situ adult hearts during I/R [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, HO-1 has been further demonstrated to be induced by dobutamine and inhibit HMGB1 release during myocardial I/R injury [11]. Importantly, cultured neonatal cardiomyocytes may present with a very stable phenotype and the contractile profile of cultured neonatal cardiomyocytes during H/R has been proved to be comparable with that of in situ adult hearts during I/R [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have suggested that AS-IV might protect from cardiomyopathy via diverse effects upon a variety of intracellular signaling pathways, including the activation of Src/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, 22) inhibiting tumor growth factor (TGF)-β1 23) and ERK1/2 signaling pathways, 24) upregulating superoxide dismutase-1 levels, 3,25) antioxidative and nitric oxide-inducing pathway, 26) and improving intracellular calcium handling. 27,28) The aim of our study is to clarify the basic electrophysiological effects of AS-IV on cardiac myocytes, and we have found that AS-IV prolonged APd, and decreased I K and I CaL in guinea-pig cardiac myocytes. The action potential is formed by multiple ion currents gated by different ion channels.…”
Section: Effects Of As-iv On Na + Currentsmentioning
confidence: 93%
“…In isolated aortic rings, astragaloside IV-induced vasodilation was attributed to the endothelium-dependent nitric oxide-cGMP pathway, in both normal and hypertensive rats, and inhibition of vessel contraction was attributed to blockage of calcium influx (Zhang et al, 2006a(Zhang et al, , 2007. In hypoxia and reoxygenation-induced injury in vitro, astragaloside IV demonstrated a protective effect by normalization of the sarcoplasmic reticulum Ca 2ϩ pump expression and prevention of depression in Ca 2ϩ handling by the sarcoplasmic reticulum (Xu et al, 2008b). The improvement by astragaloside IV of sarcoplasmic reticulum Ca 2ϩ pump function was also confirmed by its action in isoproterenol-induced myocardial injury in vivo, for which the result indicated that astragaloside IV improved cardiac function by preventing changes of Ca 2ϩ -ATPase activity and Ser16-phosphorylated phospholamban protein expression (Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 96%